The use of technology by women gari producers in Bamunkumbit village, Northwest Region of Cameroon - LENGHA, TOHNAIN Nobert (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Cassava is one of the main starchy staple foods in Cameroon with 80% of rural and urbanhouseholds consuming it and its other derivatives daily. The increase in demand for this tuber andits proceeds has led to increased prices because of high demand and consequently leading to anincrease in production exceeding the previous traditional subsistence systems. Women rely mostlyon traditional techniques to produce one of its by-products known as gari. This study focuses onthe adoption of Agricultural Technology Transfer by women gari producers in BamunkumbitNorth West Region of Cameroon and the efficiency of the adoption of the new technology. Thefactors identified as having direct impact on women producers towards adoption of appropriatetechnology are educational level, marital status, and access to funding for production. Data wascollected with the use of questionnaire, and focus group discussion (FGD) guides. Results indicatethat most rural women are eager to adopt improved technology but are hindered by their level ofeducation and the absence of farm to market roads which is a general problem affecting thecountry. It is equally obvious from the results that no modern technology could be adopted exceptthrough the valorization of the existing technological approaches.